Detection of a Mitochondrial Kinase Complex That Mediates PKA–MEK–ERK‐Dependent Phosphorylation of Mitochondrial Proteins Involved in the Regulation of Steroid Biosynthesis - Paz, Cristina del Valle (2009)
In order to achieve the goal of this article, as an example we will describe the strategies followed to analyze the presence of the multi-kinase complex at the mitochondria and the posttranslational modification of two key mitochondrial proteins, which participate in the regulation of cholesterol transport across the mitochondrial membranes and in the regulation of steroid biosynthesis. Hormones, ions or growth factors modulate steroid biosynthesis by the posttranslational phosphorylation of proteins. The question still remains on how phosphorylation events transmit a specific signal to its mitochondrial site of action. Cholesterol transport requires specific interactions in mitochondria between several proteins including a multi-kinase complex. The presence of this multi-kinase complex at the mitochondria reveals the importance of the posttranslational modification of mitochondrial proteins for its activity and functions. The activation of PKA triggers the posttranslational modification of the mitochondrial acyl-CoA thioesterase (Acot2), which releases arachidonic acid (AA) in the mitochondria, and the activation of a kinase cascade that leads to the phoshorylation of the steroidogenic acute regulatory (StAR) protein. The function of StAR is to facilitate the access of cholesterol to the first enzyme of the biosynthesis process and its induction is dependent on Acot2 and intramitochondrial AA release. Truncation of the StAR protein is associated with the steroid deficiency disease, congenital lipoid adrenal hyperplasia.